A Unique Case of Hoarseness of Voice following Left Sided Supraclavicular Block: A Case Report - Lakhe, Gajal; Poudel, Hari; Pradhan, Suresh; Dhakal, Santosh (Nepal Journal of Medical Sciences, 2020)
Supraclavicular brachial plexus block is popular for surgeries distal to the level of mid-arm. Though rare, recurrent laryngeal nerve palsy can occur in 1.3% of cases. It has been reported mostly in cases of right-sided block and only one case has been reported on the left side. We present a case of 50-year-old-female patient, who developed hoarseness of voice following a left-sided classical supraclavicular block.